The Role of Lesson Study to Improve Posing Question Skills of Teacher and Students in Problem Based Learning - Widoretno, Sri; *, Sajidan; Ramli, Murni; J, Ariyanto; S, Santoso; GA, Atika (Sebelas Maret University, 2016)
Posing question is a part of the interactions in the classroom, which represents thinking process of the person who asking question. The skill of posing question can be improved through lesson study. The research objective was to determine the role of Problem-based Learning based Lesson Study on the competence of teachers and students in asking questions. The research was a quasi-experiment, wich was participated by senior high school students as subjects of the research. Two homogenous classes was selected as samples by purposive random. Teacher and studentsâ competence was improved through Lesson Study, which consisted of plan, do and see. Questions were analyzed quantitatively and qualitatively based on revised Bloom Taxonomy. Quantity of questions was analyzed by Manova. Results of the research: 1) lesson study had significantly improved teacher and studentsâ skills on asking questions; 2) The quality of teacher and studentsâ questions expanded into high dimension of knowledge, but no metacognitive questions were found; 3) The level of cognitive of students and teacher increased to the highest level (C6), but in a few number; 4) Teacher competence was argued has relevant influence to studentsâ skills on asking question